In situ atomistic observation of disconnection-mediated grain boundary migration - Qi Zhu (Nature Portfolio, 2019)
Shear-induced grain boundary migration at the atomic level is still not well understood. Here the authors combine in situ shear testing experiments and molecular dynamic simulations to reveal the atomistic mechanism of disconnection-mediated GB migration in different gold nanostructures.